Wideband inductorless transimpedance amplifier using capacitive degeneration and negative capacitance. (15th July 2020) - Singh, Preeti; Gupta, Maneesha
Abstract: This paper presents a new wideband inductorless CMOS transimpedance amplifier (TIA) for 10Gb/s applications. In this proposed TIA, inverter‐based common‐drain active feedback topology is modified by introducing a cascode transistor to reduce input impedance. Furthermore, capacitive degeneration and negative capacitance techniques are employed by using a single capacitor. Both techniques extend the bandwidth. Mathematical analysis of the proposed TIA has been done using the small signal model to describe bandwidth extension. To verify the theoretical description, the proposed TIA is simulated using TSMC 0.18 μm CMOS technology at 1.8 V power supply with 4.3 mW power consumption. The input photodiode capacitance is 0.25 pF. Simulation results show the transimpedance gain of 51.4 dBΩ and 7.6 GHz bandwidth. The input noise current spectral density is 27 pA/√Hz.